Post-warming culture of human vitrified blastocysts with prolactin improves trophoblast outgrowth - Kenji Ezoe; Nanoha Fujiwara; Tetsuya Miki; Keiichi Kato (BMC, 2023)
Abstract Background Human embryos express the prolactin (PRL) receptor at the morula and blastocyst stages. Treatment with PRL from cleavage to the blastocyst stage improves blastocyst outgrowth on fibronectin-coated dishes. However, whether post-warming PRL treatment of blastocysts cultured without PRL could improve outgrowth competence remains unknown. Furthermore, the optimal time for post-warming PRL treatment remains to be ascertained. This study investigated the effects of PRL treatment during recovery culture on human blastocyst outgrowth and its related genes. Methods In total, 374 discarded vitrified blastocysts were randomly allocated to two groups, to be cultured with (n = 208) or without PRL (control; n = 166) for 120 min for recovery, and then plated on fibronectin-coated dishes. The expression level of PRL-interacting genes, blastocyst adhesion rate, outgrowth area, distance of trophoblast migration, and outgrowth degeneration were examined. Results The mRNA expression of ezrin, radixin, and moesin, which regulate cell adhesion and invasion by controlling actin reorganization during epithelial-to-mesenchymal transition (EMT), was stimulated by PRL treatment for 120 min. The expression of EMT-related genes, transforming growth factor β1, snail1, and twist1 was also promoted following treatment with PRL for 120 min. PRL-treated blastocysts also exhibited augmented expression of cadherin 2 and transcriptional repression of cadherin 1. Higher mRNA expression of integrin-based focal adhesion-related genes, ITGA5 and ITGB1, was observed after treatment with PRL for 120 min than in the non- and shorter-treatment groups. PRL treatment for 120 min did not alter the rate of blastocyst adhesion to fibronectin-coated dishes 96 h after the outgrowth culture assay. However, multiple linear regression analysis revealed that the outgrowth area was significantly increased in PRL-treated blastocysts. The migration distance of trophoblast cells was significantly increased and degeneration rate was significantly decreased after PRL treatment. Furthermore, a more beneficial effect of PRL treatment on blastocyst outgrowth was observed when the blastocysts were vitrified on day 5 than when they were vitrified on day 6. Conclusions Post-warming culture of human vitrified blastocysts with PRL for 120 min promoted trophoblast outgrowth in vitrified human blastocysts. Furthermore, PRL treatment may reduce outgrowth degeneration by increasing resistance to apoptosis during trophoblast migration.